The Impact of ESG Disclosure, Liquidity, and Leverage on Firm Value Mediated by Profitability Performance - Nur Hikmah; Daljono Daljono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2023)
The focus of this research is to see how the influence of ESG Disclosure, Liquidity, and Leverage on Firm Value of various companies listed on the Indonesia Stock Exchange. This research is categorized as quantitative research with data collected through Bloomberg Database Terminal. Where the sample in this study were 15 companies listed on the Indonesia Stock Exchange in 2012 to 2021 period. The collected data was processed with the help of Eviews 12 application. Based on the Eviews processing, it was found that ESG Disclosure and DER had a significant effect on Firm Value of various companies listed on the Indonesia Stock Exchange in 2012-2021 with a positive direction. Instead of it, Quick Ratio had a significant effect on Firm Value of various companies listed on the Indonesia Stock Exchange in 2012-2021 with a negative direction. The direction of positive influence means that publishing an ESG Score will increase the firm value of the company. The higher ratio of DER of the company, the more positive firm value will be for Indonesia Stock Exchange listed companies. While, the direction of negative influence means the higher ratio of liquidity of the company, the more negative firm value will be for the company.